KEWAJIBAN UTAMA NEGARA TERHADAP DISKRIMINASI PEREMPUAN SUMBA DALAM HAK MELANGSUNGKAN PERKAWINAN PADA TRADISI PITI RAMBANG: The Primary Obligation of the State Towards the Discrimination Against Sumba Women in the Right to Enter into Marriage in the Tradition of Piti Rambangin - Louisa, Monique; Notoprayitno, Maya Indrasti (Faculty of Law, Universitas Trisakti, 2025)
Discrimination against women's rights, especially in the right to marry, still occurs in Indonesia, contradicting existing legal regulations, one of which is the Piti Rambang tradition in Sumba. Women's rights are part of human rights (HAM), and as universal rights based on equality, the recognition and protection of human rights should be fulfilled for all individuals, both men and women. The state clearly plays an important role in this, and therefore, every country has the primary obligation based on human rights. This disparity forms the basis of this research problem, namely how the state’s primary obligation in the right to marry applies to the Piti Rambang tradition. This research uses normative legal research that describes the primary obligations of a state related to discrimination against women in an Indonesian custom, specifically Piti Rambang. This tradition violates the right to marry for Sumbanese women, and the state is obliged to respect, protect, and fulfill human rights. The state is expected to ensure the fulfillment of its obligations and to prevent discrimination from the Piti Rambang tradition.